CERDIK Meningkatkan Pengendalian Penyakit Tidak Menular di Indonesia: Systematic Review - Hamdan Hariawan; Diana Pefbrianti (FORUM ILMIAH KESEHATAN, 2020)
Introduction: Non-Communicable Diseases (NCD) is the highest cause of death in Indonesia. The increase in non-communicable diseases prevalence is related to unhealthy lifestyles, including smoking, consumption of alcoholic beverages, lack of physical activity, and consumption of fruits and vegetables. CERDIK is a form of Indonesia government activity program to improve the prevention and management of non-communicable diseases. CERDIK consists of a series of health check activities, building non-smoking or smoking cessation behavior, diligent physical activity, a balanced diet, adequate rest, and being able to manage stress. This review literature aims to provide an overview of the effectiveness of CERDIK in efforts to improve non-communicable diseases control in Indonesia. Methods: The method used in this systematic review began with the selection of topics, then the keyword was determined to search for journals using English through several databases, including Science direct, Ebscho, Pro-Quest, and Google Scholar. Results: 6 articles mentioned that CERDIK was effective in increasing non-communicable diseases prevention and control behavior both in terms of cognitive, attitude and skills. While 2 other articles mention the successful implementation of the government program